2014
DOI: 10.1162/jocn_a_00545
|View full text |Cite
|
Sign up to set email alerts
|

Rule Activity Related to Spatial and Numerical Magnitudes: Comparison of Prefrontal, Premotor, and Cingulate Motor Cortices

Abstract: In everyday situations, quantitative rules, such as "greater than/less than," need to be applied to a multitude of magnitude comparisons, be they sensory, spatial, temporal, or numerical. We have previously shown that rules applied to different magnitudes are encoded in the lateral PFC. To investigate if and how other frontal lobe areas also contribute to the encoding of quantitative rules applied to multiple magnitudes, we trained monkeys to switch between "greater than/less than" rules applied to either line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
2
4
2
Order By: Relevance
“…In the current study, we find that neurons in PMd and CMA are not (more than expected by chance) encoding magnitudes during the sample and delay periods. In addition, only a very small portion (6 %) of cells in CMA and PMd encoded the rule (Eiselt and Nieder 2014). This is in contrast to 24 % of rule-selective cells (Eiselt and Nieder 2014) and 25 % of sample-selective cells (current study) in the PFC.…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…In the current study, we find that neurons in PMd and CMA are not (more than expected by chance) encoding magnitudes during the sample and delay periods. In addition, only a very small portion (6 %) of cells in CMA and PMd encoded the rule (Eiselt and Nieder 2014). This is in contrast to 24 % of rule-selective cells (Eiselt and Nieder 2014) and 25 % of sample-selective cells (current study) in the PFC.…”
Section: Discussioncontrasting
confidence: 76%
“…In addition, only a very small portion (6 %) of cells in CMA and PMd encoded the rule (Eiselt and Nieder 2014). This is in contrast to 24 % of rule-selective cells (Eiselt and Nieder 2014) and 25 % of sample-selective cells (current study) in the PFC. In the current study, we found that 25 % of all recorded neurons in PFC exhibited sample selectivity for either spatial frequency, line length or numerosity stimuli, with a similar number of neurons representing each of the three different magnitude types.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations